Climate change adaptation, coffee, and corporate social responsibility: Challenges and opportunities - Gino B. Bianco (International Journal of Corporate Social Responsibility (JCSR), 2020)
Climate change is making a profound impact on agricultural production across the globe. Coffee (especially the Arabica variety) is one of the most severely affected crops. Adaptive measures are therefore needed to ensure the industry's survival. Although large coffee companies have a long history of environmental action, less is known about their strategies and attitudes related to climate adaptation. This paper attempts understand how global coffee companies are addressing climate change adaptation as part of corporate social responsibility (CSR) strategies and what barriers may exist to prevent future scale-up. To answer this question, I analyzed overall global adaptation needs and the specific needs of the coffee industry, which revealed serious financial, capacity-related, and principle-based challenges. To better understand how the industry may view climate adaptation, I reviewed CSR theoretical literature and the history of CSR within the coffee industry. Through this analysis, I determined the promotion of climate adaptation in the coffee industry can best be explained by the "Creating shared value" (CSV) framework. Using the CSV framework and an understanding of global adaptation challenges, I reviewed the CSR strategies of five major coffee companies as well as supporting literature and industry information. I find that all five companies have expansive CSR programs, yet none seriously undertake climate adaptation efforts and/or make them public. I suggest several reasons for this absence, including competing CSR priorities, lack of awareness, competition, lack of leadership, the controversial nature of climate change, and the overemphasis of certification. I end the paper with a call for more collaboration and research around the adaptation issue for the coffee industry.
Keywords: 650; Coffee; Climate change; Adaptation; Mitigation; Corporate social responsibility